L’organisation de l’expertise dans les espaces de normalisation technique - Lionel Cauchard (Revue d'anthropologie des connaissances)
This article is focused on the work of experts in technical and industrial expertise committee. It shows how the problem of environmental quality of building has been held in France by different spaces of standardization. Although these spaces are characterized by the heterogeneity of their publics and resources, informal hierarchies can be identified among the different actors according to their specialization in scientific and technical knowledge. Nevertheless specialists-experts are not completely autonomous because they have to negotiate with different stakeholders in order to make their standards attractive enough to be bought by the market. In the French context, public authorities continue to play a substantial role during the standardization process.